Moralitas dalam Novel Sesuk Karya Tere Liye Kajian Sosiologi Sastra - Apryliana, Agnes; Nurhayati, Dini (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2024)
Literary works always provide moral messages related to human traits, fighting for human rights and dignity. This analysis aims to describe the moral values ​​in the novel Sesuk by Tere Liye. The data source for this analysis is the novel Sesuk by Tere Liye with a total of 327 pages which will be published in 2022. The form of the data from this analysis is in the form of sentence excerpts in the novel Sesuk by Tere Liye which are related to moral values. The method used in this research is descriptive qualitative analysis. The approach taken in this analysis uses a moral approach. The results of the analysis are in the form of issues regarding human moral values ​​in the novel Sesuk by Tere Liye in the form of human relations with their God, human relations with themselves, human relations with other human beings